Impact of MR‐guided PET reconstruction on tau detection and quantification with [18F]‐MK‐6240: Neuroimaging / New imaging methods. (7th December 2020) - Chen, Jenny; Schramm, Georg; Ades‐Aron, Benjamin; Vahle, Thomas; Chen, Qi; Turner, Arlener D.; Royse, Sarah; Lopresti, Brian; Shepherd, Timothy M.; Osorio, Ricardo; Fieremans, Els
Abstract: Background: Tau PET offers the potential of in vivo imaging neurofibrillary tangles (NFT) in the brain to assess Alzheimer's disease (AD) progression and help guide the development of disease‐modifying treatments. In this study, we evaluate visualization and quantification of NFT using simultaneous acquisition of MRI and PET using [18F]‐MK‐6240 [1]. To overcome limitations in PET spatial resolution resulting in partial volume effects (PVE), MRI‐guided PET reconstruction using an asymmetrical Bowsher prior [2, 3] was tested. Method: Cognitively normal volunteers from the NYU Center Sleep and Brain Health Center (n=18, 15 female, age=65.4±5.6) underwent examination on a 3‐T integrated PET‐MRI system (Biograph mMR (Siemens Healthcare, Erlangen, Germany). MRI and PET were performed simultaneously; MRI contrasts included MPRAGE (1‐mm isotropic) for anatomy and ultrashort echo‐time (UTE) (1.6‐mm isotropic) for attenuation correction. [18F]‐MK‐6240 was injected intravenously and PET data was reconstructed 70‐90 min post‐injection. Standard iterative reconstruction (OSEM) (2‐mm isotropic) was compared to asymmetrical Bowsher [2, 3] reconstruction with MPRAGE prior regularization weight β=30 (1x1x2mm3). PET standard uptake value (SUV) maps were co‐registered to respective MPRAGE, and (cerebellum or pons normalized) SUVR values were extracted from FreeSurfer‐derived regions of interest (ROIs). Results: Example SUVR maps of standard PET and MR‐guided PET (Fig.1) reveal the Bowsher reconstruction to have more localized and increased focal uptake in the amygdala and cortical regions including the entorhinal, posterior cingulate and precuneus, with regional SUVR‐increases of 39%, 53%, 32%, and 16% respectively. Over all subjects (Fig.2), Bowsher reconstruction results in 30% or 48% higher SUVR, and an 64% or 84%‐increase of dynamic SUVR‐range (Fig.3) when normalized versus cerebellum or pons, respectively. These trends are emphasized for entorhinal cortex (Fig.4). Conclusions: These initial results demonstrate that MR‐guided PET reconstruction of tau data may improve NFT localization and quantification. Study limitations include small number of high uptake tau‐cases and lack of standard such as histology for comparison. Future work will compare against CSF tau‐markers, cognition and comparison to other PVE correction methods. References: [1] Betthauser et al, JNM 2018;60(1):93–99; [2] Bowsher et al, Proc. IEEE Nucl. Sci. Symp., 2004(4):2488–2492; [3] Vunckx & Nuyts, Proc. IEEE Nucl. Sci. Symp., 2010:3262–3266.